NATIONAL APPROACHES OF DETERMINING THE LEGAL STATUS OF SELF-EMPLOYED PERSONS UNDER THE LEGISLATION OF UKRAINE AND FOREIGN COUNTRIES - Bagirova, Ganna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: compare national approaches to determining the legal status of self-employed persons in the legislation of Ukraine and foreign countries. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: established that self-employment is a phenomenon which is not thoroughly studied, not fully worked out, have not created a clear rod, which would have built the structure of this concept stated different approaches to the legal status of self-employed in the legislation of different countries. Discussion: identified the urgent need for legislative legislation to maintain and develop the sphere of self-employment of the population of Ukraine and unambiguous and complete definition of the legal status of self-employed persons in the legislation of Ukraine.